Temperature dependent structure and dynamics in smectite interlayers: 23Na MAS NMR spectroscopy of Na-hectorite. Issue 22 (25th April 2019) - Nanda, Raju; Bowers, Geoffrey M.; Loganathan, Narasimhan; Burton, Sarah D.; Kirkpatrick, R. James
Abstract : 23 Na MAS NMR spectroscopy of the smectite mineral hectorite acquired at temperature from −120 °C to 40 °C shows the presence of complex dynamical processes in the interlayer galleries that depend significantly on their hydration state. Abstract : 23 Na MAS NMR spectroscopy of the smectite mineral hectorite acquired at temperatures from −120 °C to 40 °C in combination with the results from computational molecular dynamics (MD) simulations show the presence of complex dynamical processes in the interlayer galleries that depend significantly on their hydration state. The results indicate that site exchange occurs within individual interlayers that contain coexisting 1 and 2 water layer hydrates in different places. We suggest that the observed dynamical averaging may be due to motion of water volumes comparable to the dripplons recently proposed to occur in hydrated graphene interlayers (Yoshida et al. Nat. Commun., 2018, 9, 1496). Such motion would cause rippling of the T-O-T structure of the clay layers at frequencies greater than ∼25 kHz. For samples exposed to 0% relative humidity (R.H.), the 23 Na spectra show the presence of two Na + sites (probably 6 and 9 coordinated by basal oxygen atoms) that do not undergo dynamical averaging at any temperature from −120 °C to 40 °C. For samples exposed to R.H.s from 29% to 100% the spectra show the presence of three hydrated Na + sites that undergo dynamical averaging beginning at −60 °C. These sites have different numbers of H2 O molecules coordinating the Na +, and diffusion calculations indicate that they probably occur within the same individual interlayer. The average hydration state of Na + increases with increasing R.H. and water content of the clay.